A systematic approach toward progressive improvement of national antimicrobial resistance surveillance systems in food and agriculture sectors - Keck, Nicolas; Treilles, Michaël; Gordoncillo, Mary; Ivette, Ouoba Labia Irène; Dauphin, Gwenaëlle; Dorado-Garcia, Alejandro; Eckford, Suzanne; Kabali, Emmanuel; Gourlaouen, Morgane; Latronico, Francesca; Lubroth, Juan; Sumption, Keith; et al. (Frontiers in Veterinary Science, 2023)
The first Food and Agriculture Organization of the United Nations (FAO) Action Plan on antimicrobial resistance (AMR), published in 2016, identified the need to develop capacity for AMR surveillance and monitoring in food and agriculture sectors. As part of this effort, FAO has developed the “Assessment Tool for Laboratories and AMR Surveillance Systems” (FAO-ATLASS) to assist countries in systematically assessing their AMR surveillance system in food and agriculture. FAO-ATLASS includes two different modules for surveillance and laboratory assessment. Each module includes two questionnaires that collect either qualitative or semi-quantitative data to describe and score the performance of national AMR surveillance system data production network, data collection and analysis, governance, communication and overall sustainability in a standardized manner. Based on information captured in the questionnaire by trained assessors (1) tables and figures describing the outputs of the surveillance system are automatically generated (2) a Progressive Improvement Pathway (PIP) stage, ranging from “1-limited” to “5-sustainable”, is assigned to each laboratory assessed in the country, each area of the surveillance system and also to the overarching national AMR surveillance system. FAO-ATLASS allows national authorities to implement a strategic stepwise approach to improving their AMR surveillance systems via the FAO-ATLASS PIP system and provides an evidence base for actions and advocacy. The implementation of FAO-ATLASS at regional and global levels can contribute to harmonize and better coordinate strategies aimed at implementing an integrated AMR surveillance system under the One Health approach.